The Relationship Between Male and Female Youth Volunteering and Extrinsic Career Success: A Growth Curve Modeling Approach. (April 2019) - Shantz, Amanda; Banerjee, Rupa; Lamb, Danielle
Drawing from investment and statistical discrimination theories, we test a model to examine the income growth trajectories of male and female youth volunteers and non-volunteers. Using growth curve modeling for four waves of longitudinal data for the reference period 2001-2007 ( n = 7, 447), we find that male and female youth volunteers face an initial earnings disadvantage vis-à-vis youth non-volunteers; this penalty is smaller for females compared with males. However, over time, the income growth of volunteers is higher than that of non-volunteers. Male volunteers experience faster earnings growth than female volunteers. Furthermore, we find that, given the more rapid earnings growth of male volunteers relative to female volunteers, volunteering serves to widen, rather than narrow, the gender wage gap. The implications for future research and the relevance of the findings for career counselors, youth, and voluntary organizations are discussed.